PENGGUNAAN ASSOSIATION RULE MINING DALAM PENETAPAN HARGA PROMOSI, STOK, DAN PENATAAN PRODUK PADA ETALASE - Budi Raharjo (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
In the first quarter of 2017, retail in Indonesia recorded a growth of 2.5%, while in 2018 the growth was only in the range of 1% -1.5%. The cause of the slow growth is the change in the consumption pattern of the people and it will continue at the beginning of 2018. In addition, the decreasing productivity of the community at the lower middle level. As a retailer, Anterah store also faces the same thing, so anticipating a decline in sales requires an analysis of the best-selling products and how to find out the relationship between the products purchased by consumers. The association relationship between these products will be used as the basis for product arrangement, so that the frequency of products that consumers often buy can be arranged closely together so that consumers do not have to look for them longer. Market basket analysis to determine the relationship between products sold simultaneously is used to explore association rules (Association Rule Mining) which will produce products that are purchased simultaneously as a consideration for product arrangement in Anterah Retail storefront. Meanwhile, the best-selling products will be explored using the Frequent Pattern Growth method in order to obtain a ranking list of the most purchased products by consumers. This analysis is used as a basis for considering product promotion. The test results on the sales sample data obtained an average value of minimum support = 0.0025, minimum confidence = 0.610, LaPlace = 0.9985, Gain = -0.006, p-s = 0.003, Lift = 103.82, Convicting 2.5285 with a processing time of 41.456 seconds.